INTERROGATIVE PHATICS EXPRESSING DIRECTIVE MEANING IN FRENCH VERBAL COMMUNICATION - Nguyen, Minh Chinh (VNU Journal of Foreign Studies, 2023)
In verbal communication, French people often use a number of expressions including the so-called interrogative phatics to attract the attention of the participants interacting with them, or to ask the listener for approval, or to ensure that the conversation is not interrupted abnormally. In these cases, the listener needs to show by actions or words that he/she still pays attention or agrees with what has been, is being and is about to be said. This article examines how native French speakers use these interrogative phatics in everyday conversation. Qualitative and quantitative analyses reveal the characteristics of these expressions and the frequency of their use in everyday French conversation. The article also examines how linguistic means have been mobilized by native French speakers to satisfy linguistic standards and social norms as well as usage trends in different social situations in which the speaker participates.